Light affects heart rate's 24‐h rhythmicity in intensive care unit patients: an observational study. Issue 5 (14th May 2019) - Korompeli, Anna; Kavrochorianou, Nadia; Molcan, Lubos; Muurlink, Olav; Boutzouka, Eleni; Myrianthefs, Pavlos; Fildissis, Georgios
ABSTRACT: Background: Intensive care unit (ICU) patients experience two affronts to normal 24‐h rhythms: largely internal events such as medication and external factors such as light, noise and nursing interventions. Aims and objectives: We investigated the impact of light variance within an ICU on 24‐h rhythmicity of three key physiological parameters: heart rate (HR), mean arterial blood pressure (MAP) and body temperature (BT) in this patient population. Design: Patients were assigned to beds either in the 'light' or 'dark' side within a single ICU. An actigraph continuously recorded light intensity for a 24–72‐h period. Methods: Measurements of HR, MAP and BT were recorded every 30 min. Results: HR, MAP and BT did not follow 24‐h rhythmicity in all patients. Higher light exposure in the Light Side of the ICU (122·3 versus 50·6 lx) was related to higher HR (89·4 versus 79·8 bpm), which may translate to clinically relevant outcomes in a larger sample. Duration of stay, the one clinical outcome measured in this study, showed no significant variation between the groups ( p = 0·147). Conclusions: ICU patients are exposed to varying light intensities depending on bed positioning relative to natural sunlight, affecting the 24‐h rhythm of HR. Larger, well‐controlled studies also investigating the effect of relevant light intensity are indicated. Relevance to clinical practice: Light is a variable that can be manipulated in the constrained environment of an ICU, thus offering an avenue for relatively unobtrusive interventions.